The problem of early learning of foreign languages in Germanspeaking countries in modern pedagogical science - Nataliia Kohut (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the main aspects of early foreign language teaching in Germanspeakingcountries (Germany, Austria and Switzerland) in modern Pedagogics. The meaningof the term "early teaching" is defined and the teaching of foreign languages for pre-schooland primary school children is analyzed. Key words: early teaching, foreign language education, primary school, system ofeducation, multicultural surrounding.